Prothrombotic Changes in Diabetes Mellitus - Morel, Olivier; Jesel, Laurence; Abbas, Malak; Morel, Nicolas (Seminars in Thrombosis and Hemostasis, 2013)
Although our understanding of vascular pathology has greatly improved in recent years, the cellular and molecular mechanisms underlying the enhanced thrombotic propensity in type 2 diabetes mellitus (T2DM) remain incompletely characterized. Detrimental interactions between activated vascular cells (i.e., platelets, leukocytes, endothelial cells) and the vulnerable atheromatous plaque are a major determinant of the increased atherothrombotic burden in T2DM patients. Endothelial damage and accelerated senescence, impairment of the endothelial progenitor cell repair system, plaque neovascularization and inflammation, decreased clearance of detrimental molecules within the plaque, and increased expression of matrix metalloproteinases may collectively contribute to intraplaque hemorrhage and subsequent rupture. Notably, recent data demonstrates the central importance of the tissue factor-microparticle–mediated pathway in diabetic thrombophilia and cardiovascular complications. Acting as detrimental amplifiers of various biological responses (including thrombogenicity and plaque remodeling), microparticles have also emerged as a key marker of global vascular damage in T2DM patients. Available evidence suggests that targeting the tissue factor-microparticle pathway may be a promising approach for reducing the burden of the atherosclerotic complications of diabetes.
Keywords: thrombosis; microparticles; tissue factor; myocardial infarction; platelet stimulation; endothelial damage; leukocyte activation; angiogenesis